2022
DOI: 10.1007/s00415-022-11398-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain changes in patients with persistent headache after COVID-19 resolution

Abstract: Headache is among the most frequently reported symptoms after resolution of COVID-19. We assessed structural brain changes using T1- and diffusion-weighted MRI processed data from 167 subjects: 40 patients who recovered from COVID-19 but suffered from persistent headache without prior history of headache (COV), 41 healthy controls, 43 patients with episodic migraine and 43 patients with chronic migraine. To evaluate gray matter and white matter changes, morphometry parameters and diffusion tensor imaging-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…It can be interpreted as the gray matter decrease in the orbitofrontal and medial temporal lobes will make SVM classifier move toward (or classifies) CH. Interestingly, the regions with negative weights resembled the results from previous mass-univariate results, that is, involving the orbitofrontal and medial temporal lobes ( Díez-Cirarda et al, 2022 ; Planchuelo-Gómez et al, 2022 ). For example, Planchuelo-Gómez et al (2022) reported decreases in gray matter in anterior areas, including the pars orbitalis, the fusiform gyrus and the frontal pole, in patients with persistent headache after COVID-19 resolution.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…It can be interpreted as the gray matter decrease in the orbitofrontal and medial temporal lobes will make SVM classifier move toward (or classifies) CH. Interestingly, the regions with negative weights resembled the results from previous mass-univariate results, that is, involving the orbitofrontal and medial temporal lobes ( Díez-Cirarda et al, 2022 ; Planchuelo-Gómez et al, 2022 ). For example, Planchuelo-Gómez et al (2022) reported decreases in gray matter in anterior areas, including the pars orbitalis, the fusiform gyrus and the frontal pole, in patients with persistent headache after COVID-19 resolution.…”
Section: Discussionsupporting
confidence: 74%
“…For example, one of the pioneering study using the UK biobank observed gray matter reduction in patients with COVID-19, specifically in orbitofrontal cortex and parahippocampal gyrus ( Douaud et al, 2022 ). These findings are reported not only in comparison to healthy controls but also against migraineurs ( Planchuelo-Gómez et al, 2022 ).…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations